The Enigmatic Spin Evolution of Psr J0537-6910: R-Modes, Gravitational Waves, and the Case for Continued Timing - Espinoza-Romo, C (Institute of Physics Publishing, 2018)
We discuss the unique spin evolution of the young X-ray pulsar PSR J0537-6910, a system in which the regular spin down is interrupted by glitches every few months. Drawing on the complete timing data from the Rossi X-ray Timing Explorer (from 1999 to 2011), we argue that a trend in the interglitch behavior points to an effective braking index close to n = 7, which is much larger than expected. This value is interesting because it would accord with the neutron star spinning down due to gravitational waves from an unstable r-mode. We discuss to what extent this, admittedly speculative, scenario may be consistent and if the associated gravitational-wave signal would be within reach of ground-based detectors. Our estimates suggest that one may, indeed, be able to use future observations to test the idea. Further precision timing would help to enhance the achievable sensitivity, and we advocate a joint observing campaign between the Neutron Star Interior Composition Explorer and the LIGO-Virgo network. © 2018. The American Astronomical Society. All rights reserved..